The Impacts of Cord Blood Cotinine and Glutathione-S-Transferase Gene Polymorphisms on Birth Outcome - Kuan-Han Huang; An-Kuo Chou; Suh-Fang Jeng; Sharon Ng; Chia-Jung Hsieh; Mei-Huei Chen; Pau-Chung Chen; Wu-Shiun Hsieh (Elsevier, 2017)
This study aimed to investigate the association between cord blood cotinine levels and birth outcome, and to determine whether fetal metabolic gene polymorphisms of glutathione-S-transferase (GST) modulate the effect of environmental tobacco smoke exposure during pregnancy. Methods: This study included 328 maternal and neonatal pairs. Maternal and cord blood cotinine levels were measured using high performance liquid chromatography. The GST T1 (GSTT1) and GST M1 (GSTM1) polymorphisms were examined using the polymerase chain reaction method. The birth outcomes included birth weight, length, and head circumference, and the risks of having low birth weight and being small for gestational age (SGA). Results: Cord cotinine level had a dose-dependent impact on the reduction of birth weight, length, and head circumference in newborns. Elevation of cord blood cotinine concentration increased the rate of SGA and low birth weight. The neonates who had GSTT1 or GSTM1 polymorphism were associated with an increased risk of being SGA. A combination of the GSTT1 and GSTM1 null genotype exacerbated the effect of maternal environmental tobacco smoke exposure on SGA more than the presence of either genotype alone (odds ratio=8.90, 95% confidence interval=1.00-79.5). Conclusion: Cord blood cotinine adversely affects birth outcomes. GSTT1 and GSTM1 null genotype may modify the effect of cord blood cotinine on birth outcomes.